1990
DOI: 10.1111/j.1365-2141.1990.tb02583.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of prostaglandin E1 for prevention of liver veno‐occlusive disease in leukaemic patients treated by allogeneic bone marrow transplantation

Abstract: Prostaglandin E1 (PGE1) was used to prevent veno-occlusive disease (VOD) of the liver after allogeneic bone marrow transplantation (BMT) for leukaemia. It was given in continuous i.v. infusion from day--8 to day 30 after BMT at a dose of 0.3 micrograms/kg/h. The patients were studied according to the risk factors for VOD: diagnosis, intensification of the conditioning and previous liver abnormalities. The diagnosis of VOD was made on at least two of the following factors: weight gain, hepatomegaly, jaundice, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
50
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(51 citation statements)
references
References 18 publications
1
50
0
Order By: Relevance
“…Although our study was not randomized, we found a similar incidence of VOD in the no prophylaxis group as several other studies. 1,3,7,8,10,13 We confirmed previous findings that unrelated donor, decreased performance status and elevated AST are significant risk factors for developing VOD. We concluded that a significantly lower incidence of VOD developed in patients treated with Hep Ϯ PGE1 or LMWH than in the control patients.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Although our study was not randomized, we found a similar incidence of VOD in the no prophylaxis group as several other studies. 1,3,7,8,10,13 We confirmed previous findings that unrelated donor, decreased performance status and elevated AST are significant risk factors for developing VOD. We concluded that a significantly lower incidence of VOD developed in patients treated with Hep Ϯ PGE1 or LMWH than in the control patients.…”
Section: Discussionsupporting
confidence: 88%
“…[7][8][9][10][11][12] Nevertheless, these studies demonstrated that low doses of Hep could be safely administered to BMT patients. Prostaglandin E1 (PGE1) was used as a VOD prophylactic regimen by Gluckman et al, 13 who found a decreased incidence of VOD in patients treated with PGE1, whereas Bearman et al, 14 concluded that PGE1 was too toxic. Previous work has demonstrated the efficacy and safety of low molecular weight heparin (LMWH) for deep venous thrombosis prophylaxis and treatment.…”
mentioning
confidence: 99%
“…Although various drugs such as heparin, pentoxifylline, prostaglandin E1 (PGE1), ursodepxycholic acid are used to prevent VOD, their efficacy is uncertain. [19][20][21][22][23] There is no consistently effective therapy for VOD, although a few case reports recommend recombinant tissue plasminogen activator (rt-PA) as treatment. [24][25][26][27] All VOD patients in this study received continuous infusions of heparin, and two received AT-III to keep the and two received prophylactic AT-III.…”
Section: Coagulation-fibrinolysis Markersmentioning
confidence: 99%
“…As prophylaxis against hepatic VOD, UDCA, LMWH and PGE1 have been favorably reported (18)(19)(20), while conservative treatments of hepatic VOD include rt-PA, DF, AT-III and PGE1 (6,7,21). In this case, we tried all of the above -except for rt-PA -and all failed.…”
Section: Discussionmentioning
confidence: 94%